The ancestors, violence and democracy in Zimbabwe - Dube, Zorodzai (Verbum et ecclesia, 2018)
Are the departed silent in their graves or do their voices influence the way we participate in politics? While in other places their voices could be less loud, it is not so in Zimbabwe. Using Terrence Ranger and Eric Hobsbawm’s theory regarding invention of traditions, this study explores the deployment of ancestral voices in Zimbabwean politics as a strategy to legitimise political power and social hierarchy. In Zimbabwe, each cycle of election is characterised by constant reminder concerning the voices of the departed, reminding the voters that their democratic exercise through elections must align with the wishes of the nation’s ancestors such as Nehanda, Kaguvi, Chamunika and Mwari – the national god. The study consists of three parts: the first part looks into the belief in ancestors, focusing on the ancestral hierarchical order; the second part explores how the spiritual world of the ancestors in terms of its hierarchy is reflected through the spatial arrangement at the village and household levels; and the last section looks into how Mugabe utilises the ideology concerning the ancestors to maintain political power. Intradisciplinary and/or interdisciplinary implications: Through use of explanatory theories in religious studies and theology, this study unpacks the complexity of theorising politics and democracy within contexts in which the spiritual (in this case, ancestors or gods) takes precedence. After dialoguing and critiquing the current and dominant theories regarding religion across the continent, the article finds Terrence Ranger and Eric Hobsbawm’s theory regarding invented traditions the most plausible perspective to explain the interaction of religious canopies and political configurations in Zimbabwe.